Chronotropic incompetence in end-stage liver disease. - Renata Główczyńska; Sonia Borodzicz-Jażdżyk; Michał Peller; Joanna Raszeja-Wyszomirska; Piotr Milkiewicz; Krzysztof Zieniewicz; Grzegorz Opolski (PLoS ONE, 2022)
Background Cirrhosis causes alterations in the cardiovascular and autonomic nervous systems and leads to cirrhotic cardiomyopathy (CCM). CCM is defined as cardiac dysfunction characterized by an impaired systolic responsiveness to stress or exercise, and/or impaired diastolic function, as well as electrophysiological abnormalities, including chronotropic incompetence (CI), in the absence of other known cardiac disease. CI is a common feature of autonomic neuropathy in cirrhosis. The aim of the study is to assess the role of cardiac exercise stress test in the diagnosis of CCM. Methods The analysis included 160 end-stage liver disease (ESLD) patients who underwent a cardiac exercise stress test prior to the orthotopic liver transplantation. CI was defined as the inability to achieve the heart rate reserve (HRR). Pertaining to the therapy with beta-blockers: 80% of HRR was achieved in patients not taking beta-blockers and 62% in patients taking beta-blockers. Results In the analyzed population, 68.8% of patients met the criteria for CI. CI was more frequent in the more severe ESLD (with a higher MELD score and in a higher Child-Pugh class). In comparison to the viral hepatitis and other etiologies of ESLD, patients with alcoholic cirrhosis had a significantly lower rest heart rate (HR), lower maximal HR, lower median achieved percentage of maximal predicted HR (MPHR), a smaller percentage of patients achieved ≥ 85% of MPHR and a lower heart rate reserve. No significant relationship between the survival of OLT recipients and presence of chronotropic incompetence regarding to class of Child-Pugh scale, MELD score and etiology of ESLD were found. Conclusions The prevalence of CI is higher among liver transplant candidates than previously described. The altered chronotropic response may differ in regard to the severity of liver disease correlating with both the Child-Pugh and MELD scores, however CI does not seem to influence the long-term survival post OLT. Exercise stress test is a reliable, safe and useful tool for the diagnosis of CCM in liver transplant candidates and should be included in the standard cardiovascular assessment prior to OLT.